Review of an exploratory phase II FDA regulated clinical trial of a novel surgical innovation: completion of a prospective, randomized, controlled trial to compare NeoCart with the standard-of-care, microfracture, for articular cartilage repair - Kane, Marie S.; Williams III, Riley J.; DeBerardino, Thomas M.; Taylor, Dean; Ma, C. Benjamin; Anderson, Devon E.; Crawford, Dennis C. (Annals of Joint, 2018)
Background: Full thickness articular cartilage lesions cause significant morbidity, and surgical intervention is frequently applied to restore the joint surface. Current approaches of cartilage restoration have not proven to produce hyaline cartilage and have limited clinical longevity. The objective of the current study was to evaluate a novel autologous cartilage tissue implant, NeoCart, at the conclusion of the FDA-regulated exploratory phase II randomized, prospective clinical trial. The primary surgical standard-of-care, microfracture, was set by the FDA as the control. Objectives included parameter setting for the phase III trial while conducting a preliminary long-term evaluation of safety and efficacy. Methods: Patients were randomized 2:1 to NeoCart (n=21) or microfracture (n=9) surgical intervention at time of arthroscopy. Baseline demographics and patient-reported outcomes were established including: International Knee Documentation Committee (IKDC); Knee Injury and Osteoarthritis Outcome Score (KOOS) components including Pain, Activity of Daily Living, Quality of Life, Symptoms, Sports & Recreation; Short Form 36; and Visual Analog Scale Pain. Adverse events (AEs), range of motion, and patient reported outcomes were assessed annually for 5 years. Results: The treatment and control groups did not significantly differ in age, gender distribution, symptom duration, lesion size, or baseline patient reported outcomes aside from pre-surgical Visual Analog Scale Pain scores and KOOS Sports and Recreation. AE rates did not differ between treatments. The control group had greater loss to follow-up over a 5-year period. Change from baseline was significantly greater for NeoCart than for microfracture for primary end points; IKDC (1, 2 years) and KOOS Pain (1, 3, 4 years), and secondary end points; KOOS Quality of Life, Symptoms, and Sports & Recreation until 4 years. At 5 years, IKDC, KOOS Pain, Activities of Daily Living, and Quality of Life, and Short Form 36 Physical scores for both treatments improved significantly (P